CONCENTRATION OF TOXIC INGREDIENTS (HAEVY METALS AND AROMATIC HYDROCARBONS) IN ORGANS AND TISSUES OF HYDROBIONTS IN CENTRAL CASPIAN DISTRICT - S. A. Guseinova; A. A. Gadzhiev (Юг России: экология, развитие)
Abstract. Aim. Incorporation rate of heavy metals in fish is an important informative integrant index that allows estimating the impact of water pollution and fodder hydrobiont contamination on fish organisms. Unlike other contaminating anthropogenic factors of the Caspian Sea, metals are always present in the sea interacting with fish organisms many thousands times as the result of biological and chemical circuit.Methods. We analysed the grade of concentration of heavy metals in tissues and organs of hydrobionts under the program “the Central Caspian District of the Caspian Sea marine environment”. The procedure for determining metals consisted in determination of concentration of heavy metals in accordance with the methodology recommendations of atomic absorption analysis of Dagestan 52.24.28-86, with the help of atomic absorption spectrophotometer Hitachi 180-50.Results. The results after analysis of concentration of heavy metals in the tissues and organs of fish caught in the Central Caspian Sea marine environment are compared with the average annual estimation. The results obtained on the analysis of concentration of hydrocarbons in hydrobionts selected in the Central Caspian District of the Caspian Sea marine environment are within the long-term annual average data that are typical of the Northern and Middle Caspian Sea.Main conclusions. The results obtained help to form scientific foundation of ecological regulation that takes into account some ecosystems’ anthropogenic stability. Concentration of pollutants (heavy metals and hydrocarbons) in hydrobiont tissues characterizes the ecological situation on the whole of the Caspian Sea due to hydrobionts’ large-scale migrations. The analysis of the dynamics of the pollutant concentration in tissues reflects the situation created in the drilling areas; it will help forecast and avert the negative impact of hydrocarbon production on the Caspian Sea ecosystem.